1982
DOI: 10.1007/bf02141782
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidation polymorphism on blood and urine concentrations of amitriptyline and its metabolites in man

Abstract: We have measured the metabolites (demethylated and hydroxylated) of amitriptyline in a group of seven normal volunteers. They were phenotyped as extensive or poor metabolizers using debrisoquine and bufuralol. The results demonstrate that the oxidative metabolism (aliphatic hydroxylation) of amitriptyline is under the same genetic control as that of debrisoquine and bufuralol. However, phenotypic polymorphism cannot be used to predict amitriptyline blood concentration after a single oral dose, since the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Hydroxylated metabolites have also been described for other TADs like protriptyline, amitriptyline and nortriptyline (14)(15)(16)(17). Differences in the proportions of the 2 isomers could suggest that their formation depends upon a stereoselective process.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxylated metabolites have also been described for other TADs like protriptyline, amitriptyline and nortriptyline (14)(15)(16)(17). Differences in the proportions of the 2 isomers could suggest that their formation depends upon a stereoselective process.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxylation pathway is deficient in slow debrisoquine hydroxylators, but the déméth ylation pathway is not [23,25,26]. Accord ingly, plasma concentrations of unchanged amitriptyline are barely affected [23].…”
Section: Discussionmentioning
confidence: 99%
“…Amitriptyline is mainly demethylated to nortriptyline and, to a smaller extent, hydroxylated to 10-hydroxyamitriptyline; the formed nortriptyline is extensively hydroxylated to 10-hydroxynortriptylinc, which is the main urinary metabolite [23][24][25]. The hydroxylation pathway is deficient in slow debrisoquine hydroxylators, but the déméth ylation pathway is not [23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Defective oxidation is probably due to a decreased amount or absence of the polymorphic enzyme in the livers of PM patients (Gonzalez et al 1988). Pharmacokinetic studies in healthy, drug-naive EM and PM patients have in fact indicated that the to-hydroxylation of amitriptyline (Balant-Gorgia et al 1982) and nortriptyline (Mellstrom et al 1981), the 2-hydroxylation of imipramine (Br6sen et al 1986a) and desipramine (Spina et al 1987), and the hydroxylation of clomipramine (Balant-Gorgia et al 1986) are associated with the debrisoquine/sparteine phenotype. Pharmacokinetic studies in healthy, drug-naive EM and PM patients have in fact indicated that the to-hydroxylation of amitriptyline (Balant-Gorgia et al 1982) and nortriptyline (Mellstrom et al 1981), the 2-hydroxylation of imipramine (Br6sen et al 1986a) and desipramine (Spina et al 1987), and the hydroxylation of clomipramine (Balant-Gorgia et al 1986) are associated with the debrisoquine/sparteine phenotype.…”
Section: Pharmacogeneticsmentioning
confidence: 99%